Students’ Smoking Habits and Health Impact: A Case Study of Jagannath University, Dhaka (Jagannath University Journal of Life and Earth Sciences, 2025)
The present research paper was an attempt to investigate smoking behavior and its impacts on the health of young adult students of Jagannath University in Dhaka. Therefore, the specific objectives were to explore the factors influencing smoking behaviors and its physical, psychological, and socio-economic consequences on the health of the students of Jagannath University. The study was exploratory in nature. Data were collected from a total of 388 respondents using a semi-structured questionnaire. The collected data were entered and coded using MS Excel and SPSS(v-25). The results were compiled and presented in MS Word and a GIS-based map (ArcGIS 10.8) was prepared to illustrate the study area. The study revealed important insights responsible for smoking habits and related health issues of the students. These findings would contribute to the understanding of smoking behavior of students as a serious public health concern among young adults’ university students and subsequently guide some measures that might be implemented by the university authority and other relevant stakeholders to ensure smoking-free campus for all.Jagannath University Journal of Life and Earth Sciences, 10(1) 76-90